VALUABLE WASTE: Designing an interactive science centre exhibition about the plastic recycling process - Gottfridsson, Jonatan; Tjörnevik, Linus (My University, 2021)
Plastic pollution has become an increasingly considerable problem that affects both humans, animals and nature across the globe. One way to address this problem is to change peoples’ view of the value of plastic. That would in turn induce a change in the approach to plastic to be more sustainable since it would be considered more valuable. A change in approach would also cause the behavioural change that is needed to reduce the plastic pollution. Changing peoples’ view of something can and should be done in many ways. One way to do so is to develop a science centre exhibit that will trigger emotions, spread knowledge and enlighten people about the value of plastic which will function as a spark for the needed behavioural change. This master thesis, called the Valuable Waste project, was about that science center exhibit. It was carried out by the Industrial Design Engineering master programme students Linus Tjörnevik and Jonatan Gottfridsson at the Department of Industrial and Materials Science at Chalmers University of Technology. The design bureau Boid was the project initiator. The aim of the Valuable Waste project was to develop an interactive plastic recycling exhibit. The project was carried out in three phases. Phase one consisted of literature studies, observations and interviews. This phase also contained the development of the Exhibit Scoring method, with which structured and evaluating observations were conducted in order to deﬁne the characteristics of successful science centre exhibits. The result from this phase was the Successful Exhibit Guidelines list. The gathered data from phase one served as the foundation of phase two, where the concept library was formed and ﬁlled with numerous element concepts. The concepts were evaluated and morphologically put together to a ﬁrst holistic concept, Plastfabriken 1.0. In phase three Plastfabriken 1.0 was further developed and redesigned in order to make it more realizable. In this phase, user tests were conducted. Phase three resulted in a second and ﬁnal concept of the exhibit; Plastfabriken 2.0. Plastfabriken 2.0 is a real working PET recycling machine that is developed to be the centerpiece of an exhibition at the science centre Universeum. It consists of the necessary elements needed for a plastic recycling process; cleaning, shredding, washing, drying and creating, and does thus have the function to recycle used PET into new molded plastic parts. Each element is designed to, according to the Successful Exhibit Guidelines, have an intriguing and enjoyable user interaction.